Valley of the giant skeletons - Stilton, Geronimo; Cernuschi, Claudio; Aliprandi, Christian (New York : Scholastic, 2008)
Geronimo's cousin Trap finds a map in their Uncle Wally's trunk and they follow it to Mongolia looking for treasure.
English translation from the Italian of La Valle degli Scheletri Giganti by Edizioni Piemme S.p.A.
Keywords: Treasure troves -- Juvenile fiction; Stilton, Geronimo (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction